2010
DOI: 10.2320/matertrans.m2010013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Microstructures and Tensile Properties of an Fe-30Mn-8.5Al-2.0C Alloy

Abstract: Owing to the presence of a large amount of fine (Fe,Mn) 3 AlC carbides within austenite () matrix, the tensile property of the Fe-30%Mn-8.5Al%-2.0%C (in mass%) alloy in the as-quenched condition was clearly superior to that of the as-quenched FeMnAlC (C 5 1:3%) alloys investigated by previous workers. After being aged at 823 K for 3 h, the present alloy could possess high yield strength up to 1262 MPa with an excellent 32.5% elongation. With almost equivalent ductility, the yield strength obtained was about 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…It should also be noted that the drop of yield strength after the peak strength increment does not necessarily mean that the precipitates are overaged and Orowan looping takes place. Grain boundary precipitation that weakens the grain boundaries can also contribute to a loss of yield strength [26]. Orowan looping mechanism also does not mean a strength reduction, as Gutierrez-Urrutia and Raabe [27] and Sun et al [39] showed a great Orowan strengthening but at a great expense of ductility.…”
Section: The Strengthening Mechanisms Of Nano-scale Precipitates Strementioning
confidence: 99%
See 4 more Smart Citations
“…It should also be noted that the drop of yield strength after the peak strength increment does not necessarily mean that the precipitates are overaged and Orowan looping takes place. Grain boundary precipitation that weakens the grain boundaries can also contribute to a loss of yield strength [26]. Orowan looping mechanism also does not mean a strength reduction, as Gutierrez-Urrutia and Raabe [27] and Sun et al [39] showed a great Orowan strengthening but at a great expense of ductility.…”
Section: The Strengthening Mechanisms Of Nano-scale Precipitates Strementioning
confidence: 99%
“…This is not necessarily to be the case. Haase et al [7], Chooi et al [50], and Lin et al [26] reported great ductility (~55%) in the quenched and homogenized austenitic Iron-Manganese-Aluminium-Carbon (Fe-Mn-Al-C) steels that contain a low volume fraction of fine shearable κ-carbides. After aging, the ductility reduces with the increasing volume fraction and size of κ-carbides [7].…”
Section: The Effects Of Precipitates On Slip Systems and Dislocation-mentioning
confidence: 99%
See 3 more Smart Citations